Dr Association of bone morphogenetic protein 15 and growth differentiation factor 9 with litter size in livestock: a review study - Majeed Hameed Ajafar; Alaa Hasan Kadhim; Tahreer Mohammed Al-Thuwaini; Mohammed Baqur Sahib Al-Shuhaib; Tamadhur Hani Hussein (Acta Scientiarum. Animal Sciences, 2022)
. Litter size is one of the crucial factors in livestock production and is of high economic value, which is affected by ovulation rate, hormones, and growth factors. Growth factors play a multifaceted role in reproductive physiology. This review aims to investigate the association of bone morphogenetic protein 15 (BMP15) and growth differentiation factor 9 (GDF9) with litter size in livestock. The transforming growth factor β (TGF- β) superfamily includes more than 34 members; GDF9 and BMP15 are among the most significant factors for regulating fertility and litter size in most livestock species. Ovarian follicles release BMP15 and GDF9 that are involved in the maturation of primary follicles into the basal form, proliferation of granulosa and theca cells, steroidogenesis, ovulation, and formation of the corpus luteum. Besides, these factors are highly expressed in oocytes and are necessary for female fertility and multiple ovulation in several livestock species. Animals with two inactive copies of these factors are sterile, while those with one inactive copy are fertile. Thus, the present review provides valuable information on the association of BMP15 and GDF9 with litter size in livestock that can be used as biological markers of multiple ovulation or for improving fertility in livestock.